Memories of Kings of Israel and Judah within the Mnemonic Landscape of the Literati of the Late Persian/Early Hellenistic Period: Exploratory Considerations. Issue 1 (2nd January 2019) - Ben Zvi, Ehud
ABSTRACT: This article explores, from a perspective informed by Social Memory studies, memories of kings of Judah (/Israel) in three different corpora (the Deuteronomistic Historical Collection, the Prophetic Book Collection and Chronicles). It draws attention to the interdependence between memories of kings and other characters populating the world of memory evoked by each of these corpora and explores the ways in which the worlds of memory evoked by each of them interacted, informed and balanced each other within what we may call the "comprehensive mnemonic system" of the literati. The article sheds light on generative grammars governing systems of preferences and dis-preferences for certain types of memories of kings in each of the corpora and across them, and at times, even across cultures, and highlights that the world of memory of the Yehudite literati of the late Persian/early Hellenistic period was shaped by a consistency of inconsistency, and an overall coherence manifested through a seeming lack thereof that served well the social reproduction of the group.